2006
DOI: 10.1111/j.1365-294x.2006.02976.x
|View full text |Cite
|
Sign up to set email alerts
|

Fat‐tailed gene flow in the dioecious canopy tree species Fraxinus mandshurica var. japonica revealed by microsatellites

Abstract: Pollen flow, seed dispersal and individual reproductive success can be simultaneously estimated from the genotypes of adults and offspring using stochastic models. Using four polymorphic microsatellite loci, gene flow of the wind-pollinated and wind-seed-dispersed dioecious tree species, Fraxinus mandshurica var. japonica, was quantified in a riparian forest, in northern Japan. In a 10.5-ha plot, 74 female adults, 76 male adults and 292 current-year seedlings were mapped and genotyped, together with 200 seeds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 57 publications
5
115
2
Order By: Relevance
“…By means of parentage analysis on established juveniles, Troupin (2005) found in Pinus halepensis colonization events over 500 m long, and Bacles et al (2006) recorded individuals established up to 1.4 Km from their mother tree in a fragmented population of F. excelsior. Long-distance dispersal and establishment events were also detected in other tree species by Goto et al (2006) and Hardesty et al (2006) using the same approach. We found that the probability of reaching distances as long as 2 Km is still high, especially considering the large reproductive output of conifers, and how taking into account MDDs provides a better estimation of the tail of the curve, reducing underestimation errors.…”
Section: Discussionmentioning
confidence: 78%
“…By means of parentage analysis on established juveniles, Troupin (2005) found in Pinus halepensis colonization events over 500 m long, and Bacles et al (2006) recorded individuals established up to 1.4 Km from their mother tree in a fragmented population of F. excelsior. Long-distance dispersal and establishment events were also detected in other tree species by Goto et al (2006) and Hardesty et al (2006) using the same approach. We found that the probability of reaching distances as long as 2 Km is still high, especially considering the large reproductive output of conifers, and how taking into account MDDs provides a better estimation of the tail of the curve, reducing underestimation errors.…”
Section: Discussionmentioning
confidence: 78%
“…Immigration rates estimated using the neighborhood model are a function of the dispersal kernel and are based on the assumption that the neighborhood is circular (Goto et al. 2006) resulting in a bias when the populations are linear.…”
Section: Resultsmentioning
confidence: 99%
“…Inferences about mating patterns and their association with ecological parameters such as distance, density, flowering and fragmentation are often reported in the literature based on single populations or multiple populations of different size, condition and level of genetic isolation (Goto et al. 2006; Geng et al. 2008; Llaurens et al.…”
Section: Discussionmentioning
confidence: 99%
“…With a neighborhood size of N, we can consider that a fraction a ¼ R N 0 f ðrÞ2pr@r of dispersal events occurs inside the neighborhood whereas the complementary fraction 1 À a ¼ R 1 N f ðrÞ2pr@r occurs outside the neighborhood (Goto et al, 2006). With an infinite neighborhood size, we consider that N is half of the maximum distance between potential parents in a patch network in order to ensure that all individuals are included in the neighborhood.…”
Section: Dispersal Kernelmentioning
confidence: 99%
“…With an infinite neighborhood size, we consider that N is half of the maximum distance between potential parents in a patch network in order to ensure that all individuals are included in the neighborhood. The fraction 1 À a can be considered as the expected immigration rate-of seed or pollen-if the dispersal kernel is the only dispersal source (Goto et al, 2006). Comparison of these expected and estimated rates (ms and mp) allows an estimate of all random processes (for example, long-distance dispersal) that are not captured by the kernels (Goto et al, 2006).…”
Section: Dispersal Kernelmentioning
confidence: 99%